1996
DOI: 10.1139/m96-128
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of fatty acid patterns of coryneform bacteria and related taxa

Abstract: A numerical study of the fatty acid patterns of 263 reference strains belonging to the genera Arthrobacter, Aureobacterium, Brevibacterium, Cellulomonas, Clavibacter, Corynebacterium, Curtobacterium, Erysipelothrix, Microbacterium, and Rhodococcus was undertaken based on cultural and chemical standardized techniques. Clustering was by the unweighted pair group method using the correlation coefficient. Two cluster groups could be defined at the 62% level, one containing strains characterized by saturated and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
427
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 1,060 publications
(429 citation statements)
references
References 28 publications
1
427
0
1
Order By: Relevance
“…For whole-cell fatty acid analysis, the bacteria were grown on TSB agar for 48 h at 28 "C and two to four loopfuls of bacterial cells were scraped from the Petri dish. Fatty acid methyl esters were obtained by saponification, methylation and extraction of the cells as described previously (Kampfer & Kroppenstedt, 1996). The fatty acid methyl ester mixtures were separated using the model 589814 microbial identification system (Sasser, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…For whole-cell fatty acid analysis, the bacteria were grown on TSB agar for 48 h at 28 "C and two to four loopfuls of bacterial cells were scraped from the Petri dish. Fatty acid methyl esters were obtained by saponification, methylation and extraction of the cells as described previously (Kampfer & Kroppenstedt, 1996). The fatty acid methyl ester mixtures were separated using the model 589814 microbial identification system (Sasser, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Amino acid analysis of wholecell hydrolysates followed the procedures described by Stanek and Roberts (39). The fatty acids methyl esters were prepared from 40-80 mg wet cells and analyzed as previously described (19,32,35) and trimethylsilylated devivatives of mycolic acids according to Klatte et al (23). Genomic DNA extraction and PCR amplification was performed as described by Rainey et al (33).…”
Section: Characterization Of the Isolatementioning
confidence: 99%
“…The polyamine pattern of strain RE35F\1 T contained predominantly spermidine and lacked sym-homospermidine (Vybiral et al, 1999), which supports its close relationship with Erythrobacter and Erythromicrobium (Hamana & Takeuchi, 1998). Fatty acid analysis by GLC, according to the standard protocol of the Microbial Identification system (MIDI) as described by Ka$ mpfer & Kroppenstedt (1996), showed that the major fatty acid of the cellular lipids of RE35F1 T and RE10F\45 is octadecenoic acid (18 : 1 ω7c) ; 2-hydroxymyristic acid (14 : 0 2-OH) was also present in both strains (Table 1). Furthermore, the polar lipid fingerprints of RE35F1 T and RE10F\45 obtained by twodimensional TLC (Vybiral et al, 1999) were essentially identical and, again, highly similar to those of Erythrobacter litoralis DSM 8509 T and Erythrobacter longus LMG 3982 T (E. B. M. Denner, unpublished Strains : 1, Erythrobacter citreus (n l 2) ; 2, Erythrobacter litoralis DSM 8509 T ; 3, Erythrobacter longus LMG 3982 T ; 4, Erythromicrobium ramosum DSM 8510 T .…”
Section: Chemotaxonomymentioning
confidence: 99%